P681 Ustekinumab therapy induced clinically meaningful improvement and remission as measured by the Inflammatory Bowel Disease Questionnaire: Results from the phase 3 UNIFI induction and maintenance studies. (25th January 2019) - Sands, B E; Han, C; Zhang, H; Johanns, J; Szapary, P; Marano, C; Leong, R W; Danese, S
Abstract: Background: The UNIFI studies evaluated the safety and efficacy of ustekinumab (UST) intravenous (IV) induction and subcutaneous (SC) maintenance in patients with moderately to severely active ulcerative colitis (UC). Here, we present patient-reported outcomes from the Inflammatory Bowel Disease Questionnaire (IBDQ). Methods: In the induction study, eligible patients were randomised to a single IV dose of placebo (PBO, n = 319), UST 130 mg ( n = 320), or UST ~6 mg/kg ( n = 322). Patients who were in clinical response 8 weeks after receiving UST induction were eligible for the maintenance study and were randomised to SC PBO ( n = 175), UST 90 mg q12w ( n = 172), or UST 90 mg q8w ( n = 176). The IBDQ is a 32-item questionnaire with 4 dimensions: bowel symptoms, systemic symptoms, emotional function, and social function. The total score ranges from 32 to 224, higher scores indicate better quality of life, a score ≥170 indicates remission, and a change ≥16 or >20 points was defined as clinically meaningful. Results: Mean total IBDQ scores at induction baseline ranged from 126.0 to 127.4 and were comparable across treatment groups (Table 1). Eight weeks after IV induction, patients receiving UST reported significantly greater improvement in mean IBDQ scores, and greater proportions of patients achieved clinically meaningful improvements from baseline and IBDQ remission compared with PBO ( p < 0.001 for all comparisons of UST vs. PBO). Through 44 weeks of the maintenance study, mean IBDQ scores worsened in the PBO group, were maintained in the UST q12w group, and improved in the UST q8w group (Table 2, p < 0.001). Significantly greater percentages of patients in the UST groups achieved or maintained clinically meaningful improvement ( p < 0.01) or IBDQ remission ( p < 0.02) through Week 44 compared with PBO. Patients receiving UST induction showed greater improvement in each of four domain scores of the IBDQ at Week 8 compared with PBO, and the improvements were sustained through 44 weeks of maintenance. Conclusions: Patients reported significantly greater improvements in IBDQ scores with UST IV induction compared with PBO. In patients who responded to UST IV induction, significantly greater proportions of patients who received UST SC maintenance sustained the improvements achieved during induction through Week 44, including remission, compared with PBO.